Jung's Archetypes of Persona and Shadow in Wilde's the Picture of Dorian Gray and Stevenson's Dr. Jekyll and Mr. Hyde - Dyah Kurniawati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
As a mirror of real life, literature contains things happening in the life of human beings and their surroundings. A careful study of literary works represents a way to add experience about life and also to gain knowledge about human life with all of their problems. The two novels being discusses in this article are Oscar Wilde‟s The Picture of Dorian Grayand Robert Louis Stevenson‟s Dr. Jekyll and Mr.Hyde.This article will be analyzed by using Carl Gustav Jung‟s archetypes theory in order to make a comparative study through both of those novels. Thus, this study concerns to Jung‟s archetypes of persona and shadow. The method of the research is descriptive text analysis. At the same time, the article writer also used comparative study. It was due to the aims of this study, which was to compare two literary works of the same country.The results of this study show the different achievements of persona and shadow through the representation of the characters of Dorian Gray in The Picture of Dorian Gray and Dr. Henry Jekyll in Dr. Jekyll and Mr. Hyde. The similarity of the two novels lies on the theme namely ways on fulfilling one‟s desire toward physical condition, while the differences are lie in the ways to achieve the goals of the main characters. In Wilde‟s The Picture of Dorian Gray, the main character, Dorian Gray fails to achieve his physical perfectness of eternal youth because he did it in naturally, he trades his soul to get it. In Stevenson‟s Dr. Jekyll and Mr. Hyde, Dr. Jekyll successes to achieve his insane experiment to release the good side and bad side of human in the form of different appearance. Then the writer comes to the conclusion that to attain his goal and desire. Firstly, he must be aware of the effect for the things he did. It means that an individual must be responsible for his own decision to do what he thinks is right. Secondly, one must sincerely accept the power of nature. It means that an individual has to be able to overcome the temptation that comes to him/her related to physical condition to achieve their acceptance toward nature‟s gift. By having these two factors, an individual will be able to achieve his or her acceptance toward the power of nature and accept what God has given him or her and live good life.